Combination of S‐adenosylhomocysteine and scriptaid, a non‐toxic epigenetic modifying reagent, modulates the reprogramming of bovine somatic‐cell nuclear transfer embryos. Issue 1 (17th December 2013) - Zhang, Hui; Wang, Yongsheng; Sang, Yuankun; Zhang, Yong; Hua, Song
SUMMARY The goal of this study was to improve the development of bovine somatic‐cell nuclear transfer (SCNT) embryos by optimizing the combination of DNA methyltransferases inhibitor S‐adenosylhomocysteine (SAH) and histone deacetylase inhibitor Scriptaid (SPD). A. 4 × 4‐factor design of different drug combinations (0, 0.75, 1.0, and 1.5 mM SAH and 0, 5, 250, and 500 nM SPD) was used to identify an optimal combination of 0.75 mM SAH and 250 nM SPD that improved the developmental competence of bovine SCNT embryos. Further experiments using this combination revealed that methylation levels of CpG islands near exon 1 of the pluripotent gene SOX2; the epigenetic‐related gene HDAC3 and DNMT3a; imprinted genes XIST and PEG3; as well as apoptosis‐related genes BCL2 and BAX were returned to levels similar to those of in vitro fertilized (IVF) embryo after treatment, which also normalized transcript levels for these genes. This combination also returned global DNA methylation to a normal level, correcting H4K12ac levels while enhancing H3K9ac levels. Thus, the combined application of 0.75 mM SAH and 250 nM SPD can significantly improve the reprogramming of bovine SCNT embryos by stabilizing how embryos utilize their genomes. Mol. Reprod. Dev. 81: 87–97, 2014. © 2013 Wiley Periodicals, Inc.